2010
DOI: 10.1111/j.1365-2222.2010.03476.x
|View full text |Cite
|
Sign up to set email alerts
|

Antigen dose‐dependent suppression of murine IgE responses is mediated by CD4CD8 double‐negative T cells

Abstract: Our data demonstrate that CD4(-)CD8(-) dnT cells play a major role in the regulation of IgE responses induced by high antigen doses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…This was associated with decreased eosinophil recruitment, decreased Th2 cytokines to recall in vitro stimulation, and reduction in sera IgE levels. Consistent with our findings, Aguilar-Pimentel et al and others have shown that hi-dose intraperitoneal sensitization leads to modulation of Th2 in the allergic asthma model [12]. Data herein suggest that this effect in our model was not associated with a dominant Th1 response, as hi-dose sensitization was found here to have suppressed IFN-g levels indicated by recall stimulation of LN T cells in vitro.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This was associated with decreased eosinophil recruitment, decreased Th2 cytokines to recall in vitro stimulation, and reduction in sera IgE levels. Consistent with our findings, Aguilar-Pimentel et al and others have shown that hi-dose intraperitoneal sensitization leads to modulation of Th2 in the allergic asthma model [12]. Data herein suggest that this effect in our model was not associated with a dominant Th1 response, as hi-dose sensitization was found here to have suppressed IFN-g levels indicated by recall stimulation of LN T cells in vitro.…”
Section: Discussionsupporting
confidence: 93%
“…HI-dose intraperitoneal sensitization in mice is a highly reproducible model to induce an impairment of allergic Th2 responses [6-12], and thereby is of particular utility toward elucidation of natural mechanisms that modulate allergy. Evidence has led to the hypothesis that such an altered response is merely a secondary effect of priming a Th1 dominant response—which in turn suppresses other Th subsets such as Th2 [6-8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low exposure is likely to be one of the reasons. A weak antigen signal is known to instruct dendritic cells to signal T cells to initiate a TH2‐polarized response (75, 76) and affects another T‐cell population as well (77). This would have an effect on the B‐cell response to the antigen as a whole, but not necessarily at the level of B‐cell paratope specificity.…”
Section: Techniques To Identify (Partial) Epitopesmentioning
confidence: 99%
“…They found little difference in the response to crude peanut extract between peanut allergic and peanut sensitized children with Th1 and Th2 cytokine production from both, but allergic children had enhanced responses to purified allergens [58]. Further insight into the mechanisms involved in sensitization and particularly the effect of the dose of allergen was provided by Barwig et al [59]. They compared in a mouse model of sensitization to keyhole limpet antigen, the effect of a high and low dose of allergen on sensitization.…”
Section: Th Cellsmentioning
confidence: 99%